Developmental Plasticity of Rice Root System Grown under Mild Drought Stress Condition with Shallow Soil Depth; Comparison between Nodal and Lateral roots. (2nd July 2016) - Kameoka, Emi; Suralta, Roel Rodriguez; Mitsuya, Shiro; Yamauchi, Akira
Abstract: The plasticity in root system development (RSD) is a key trait for the adaptation of rice to mild drought. However, the enhanced RSD due to the plasticity may not be always a sole function of promoted lateral root (LR) production, but also of the integrated responses of nodal root (NR) development. In this study, we aimed to evaluate the effects of mild drought intensities on the development of the NR and LR, and their contribution to the entire RSD. We used six genotypes including KDML105 ( indica, lowland adapted), a high lateral rooting ability genotype. The plants were grown up to heading or maturity stage for two years under soil with limited soil depth (20 cm) assuming the presence of the hardpan and at different moisture gradients generated by the line source sprinkler system. The effects of drought intensities generally differed between the development of NR and LR. In both years, all genotypes showed highest LR development under mild drought stress intensities. However, in some genotypes including KDML105, NR development was maintained in a limited soil moisture range only, which was narrower and wetter than that in which LR plasticity was expressed. Furthermore, the entire RSD was maintained only when both the NR and LR were simultaneously promoted or maintained. These results suggest that the NR have less plasticity than the LR in response to drought and the contribution of the plasticity in LR development to the entire RSD is dependent on both the soil moisture and nodal rooting ability.